Luminal Surface Plasma Treatment of Closed Cylindrical Microchannels: A Tool toward the Creation of On-Chip Vascular Endothelium - Černík, Marek; Poláková, Kamila; Kubala, Lukáš; Vítečková Wünschová, Andrea; Mac Gillavry Danylevska, Anna; Pešková, Michaela; Víteček, Jan (ACS biomaterials science & engineering, 2023)
On-chip vascular microfluidic models provide a great tool to study aspects of cardiovascular diseases in vitro. To produce such models, polydimethylsiloxane (PDMS) has been the most widely used material. For biological applications, its hydrophobic surface has to be modified. The major approach has been plasma-based surface oxidation, which has been very challenging in the case of channels enclosed within a microfluidic chip. The preparation of the chip combined a 3D-printed mold with soft lithography and commonly available materials. We have introduced the high-frequency low-pressure air-plasma surface modification of seamless channels enclosed within a PDMS microfluidic chip. The plasma treatment modified the luminal surface more uniformly than in previous works. Such a setup enabled a higher degree of design freedom and a possibility of rapid prototyping. Further, plasma treatment in combination with collagen IV coating created a biomimetic surface for efficient adhesion of vascular endothelial cells as well as promoted long-term cell culture stability under flow. The cells within the channels were highly viable and showed physiological behavior, confirming the benefit of the presented surface modification.
Keywords: hydrofobní a hydrofilní interakce; PDMS; Cell Culture Techniques; plasma oxidation; cévní endotel; buněčné kultury; Hydrophobic and Hydrophilic Interactions; endothelial cell; Microfluidics; 3D printing; in vitro model; mikrofluidika; surface modification; endoteliální buňky; Endothelium, Vascular; Endothelial Cells